Numerical Simulation Study on the Volumetric Efficiency Loss of CO2 Swash Plate Axial Piston Pumps - Xiyin Wang; Sanping Zhou (Applied Sciences)
With the aim of addressing the low volumetric efficiency of CO2 swashplate axial piston pumps, the influence of four volumetric losses—loss of the CO2 compression retention volume, leakage volume loss of the port pair, leakage volume loss of the plunger pair, and leakage volume loss of the slipper pair—on volumetric efficiency was analyzed using a transient numerical simulation method. The numerical simulation results showed that the real physical property model can accurately describe the compression retention characteristics of CO2 under high-pressure conditions. CO2 compression retention volume loss accounted for 28.6% of the volumetric efficiency and was the main factor causing low volumetric efficiency of the piston pump. Leakage volume losses of the slipper pair, the flow distribution pair, and the plunger pair accounted for about 3.4%, 1.5%, and 0.5% of the volumetric efficiency, respectively. These research results provide a reference for volumetric efficiency loss analyses of piston pumps.